Overview of DKMA's role in Agricultural Knowledge Management - Malhotra, S K (Indian Farming, 2024)
This article provides an overview of the Directorate of Knowledge Management in Agriculture (DKMA), tracing its evolution since its establishment in 1929. Formerly known as the Publications and Information Division, DKMA has become a vital Nodal Centre for ICAR, focusing on information, communication, and knowledge management. The article highlights DKMA's key contributions, including the publication of research journals, magazines, handbooks, textbooks, and extensive online resources. It emphasizes the Directorate's role in maintaining a global presence through open-access portals and social media. DKMA's involvement in significant events, such asRepublic Day showcases and the MACS G-20 meeting, reflects its impactful initiatives. The article concludes by underlining DKMA's ongoing commitment to diverse publications, solidifying ICAR's prominence in the agricultural sector.